2020
DOI: 10.3390/ijms21249469
|View full text |Cite
|
Sign up to set email alerts
|

Restraint Stress in Mice Alters Set of 25 miRNAs Which Regulate Stress- and Depression-Related mRNAs

Abstract: In the present study, we aim to identify the effect of restrain stress (RS) on the expression of miRNAs in mouse serum. We used three genotypes of animals (mice with knock-out of the gene-encoding norepinephrine transporter, NET-KO; C57BL/6J, and SWR/J) which had previously been shown to display different sensitivity to RS, and focused on miRNAs which were altered by RS in the serum of all three genotypes. An analysis of miRNAs expression allowed for the identification of a set of 25 differentially expressed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…In the present study, we examined the differentially expressed miRNA profile in a chronic unpredictable mild stress (CUMS)-induced rat model of depression versus normal controls using a high-throughput microarray. We found that miR-26a-3p, a potential miRNA that is responsible for regulation of mRNA-encoding proteins related to stress and depression (23), showed a significant differential expression within the dentate gyrus (DG) hippocampus of CUMS versus control rats and interacted with the phosphate and tension homology deleted on chromsome ten (PTEN)-phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) signaling pathway. Complementing these findings, the knock-down of miR-26a-3p in DG regions of control rats accelerated neuronal deterioration and induced depression-like behaviors, whereas an up-regulation of miR-26a-3p within DG regions of CUMS-induced depressed rats rescued neuronal deterioration and depression-like phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we examined the differentially expressed miRNA profile in a chronic unpredictable mild stress (CUMS)-induced rat model of depression versus normal controls using a high-throughput microarray. We found that miR-26a-3p, a potential miRNA that is responsible for regulation of mRNA-encoding proteins related to stress and depression (23), showed a significant differential expression within the dentate gyrus (DG) hippocampus of CUMS versus control rats and interacted with the phosphate and tension homology deleted on chromsome ten (PTEN)-phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) signaling pathway. Complementing these findings, the knock-down of miR-26a-3p in DG regions of control rats accelerated neuronal deterioration and induced depression-like behaviors, whereas an up-regulation of miR-26a-3p within DG regions of CUMS-induced depressed rats rescued neuronal deterioration and depression-like phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these results indicate that lower levels of certain miR-NAs enable an organism to better cope with stress, probably via reduction of the main effect of miRNAs, i.e., the inhibition of translation processes. On the other hand, our previous studies [4,5] showed that the effect of RS was different in the mouse serum, i.e., more miRNAs were downregulated (10) than upregulated (4) in the PFC, while in the serum, the relations were the opposite (15 miRNAs were upregulated vs. 10 that were downregulated). Among these miRNAs were mmu-miR-99a-5p and mmu-miR-23a-3p, which were also detected in the PFC in the present study.…”
Section: Discussionmentioning
confidence: 86%
“…In the previous study, we were able to identify numerous miRNAs that are present in the mouse serum, which differentiated three strains of mice depending on their response to restraint stress (RS) [4,5]. These miRNAs might be regarded as biomarkers of stress resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since they are released by cells and circulate in biological fluids such as blood, microRNAs can easily be measured with a diverse range of robust techniques, such as small RNA sequencing, microarrays, and quantitative polymerase chain reaction (PCR). In recent studies, using three genotypes of mice that were shown to display different sensitivity to restraint stress (RS) [ 40 ], we identified a set of 25 miRNAs altered by RS [ 41 ]. These miRNAs are responsible for regulating mRNAs encoding proteins that are key to the main hypotheses of depression (e.g., monoaminergic receptors and their transporters, neurotrophic factors, neuropeptides and their receptors, glucocorticoid receptors, glutamate and GABA receptors and their transporters, as well as interleukins, TNF, interferon, and their receptors).…”
Section: Microrna As Biomarkers Of Stress Resiliencementioning
confidence: 99%